2019
DOI: 10.9778/cmajo.20180064
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unnecessary urine culturing and antibiotic overprescribing in long-term care: a before-and-after analysis

Abstract: ates of antibiotic use in long-term care homes are highly variable and this variability is not associated with characteristics of long-term care residents. 1 However, high rates of antibiotic use are associated with antibiotic resistance and Clostridium difficile infection. 2-4 Antibioticassociated adverse events could be reduced if antibiotic overuse in long-term care was reduced. 5 Over 30% of antibiotics prescribed in long-term care are for urinary indications. 6 One practice that can contribute to overuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…Lastly, since we ran our searches in November 2018, we have identified three more articles describing before-after studies of interventions to improve antibiotic prescribing in LTCFs that meet our inclusion criteria. One study evaluated the impact of an educational intervention to improve antibiotic use for UTIs in 10 Canadian LTCFs and reported a 26% decrease (adjusted incidence rate ratio=0.74, 95% CI: 0.47 to 0.74) in the overall number of antibiotic prescriptions per 1000 resident days 10. The second study, in seven Canadian LTCFs, reported a decrease in the use of antibiotics for asymptomatic bacteriuria from 90% pre-intervention to 62.9% post-intervention (p=0.003), following an educational intervention 73.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, since we ran our searches in November 2018, we have identified three more articles describing before-after studies of interventions to improve antibiotic prescribing in LTCFs that meet our inclusion criteria. One study evaluated the impact of an educational intervention to improve antibiotic use for UTIs in 10 Canadian LTCFs and reported a 26% decrease (adjusted incidence rate ratio=0.74, 95% CI: 0.47 to 0.74) in the overall number of antibiotic prescriptions per 1000 resident days 10. The second study, in seven Canadian LTCFs, reported a decrease in the use of antibiotics for asymptomatic bacteriuria from 90% pre-intervention to 62.9% post-intervention (p=0.003), following an educational intervention 73.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have estimated that between 47% and 70% of residents receive a course of antibiotics annually, and that between 77% to 88% of infections are treated with an antibiotic 7–9. Approximately 50% of these prescriptions are judged to be inappropriate,9 with inappropriate treatment of urinary tract infections and respiratory tract infections common in LTCF residents 7–12. Thus, there is considerable scope for improving antibiotic use in LTCFs.…”
Section: Introductionmentioning
confidence: 99%
“…We determined that a minimum of 32 LTCHs would be required to detect a statistically significant difference between treatment and control groups with 80% power and 5% significance for rates of urine cultures performed. This estimate was based on the following assumptions: an event rate difference of −1.0 per 1000 resident days, control event rate of 3.2 per 1000 resident days, an average home bed size of 160 13 and an assumption that the coefficient of variation was 0.25. Using similar methods but with an event rate difference of −0.6 and control event rate of 1.5 per 1000 resident days, we determined that 22 LTCHs would be required for rates of urinary antibiotic prescriptions.…”
Section: Sample Sizementioning
confidence: 99%
“…Previous studies of the UTI Programme and similar multimodal programmes have described experts delivering on-site support. 13 14 These types of supports present an opportunity to build the capacity of organisations to effectively implement practice change; however, tailored onsite visits may not be feasible beyond a pilot stage due to resource intensity. To help scale the UTI Programme in Ontario, Canada, virtual learning collaboratives were selected as a means to maintain support for implementation while also bringing together multiple long-term care homes (LTCHs) to facilitate shared learning.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal interventions to support these practice change statements are not yet known. Many organizations across Canada, for example, Alberta Health Services, Public Health Ontario and the Association of Medical Microbiology and Infectious Diseases, have developed tools to reduce overdiagnosis and subsequent overtreatment of UTI (24)(25)(26). One common theme is the need for an objective, standardized approach to the diagnosis of UTI in the long-term care resident population using evidence-based criteria so that all health care providers, patients and substitute decision-makers are aligned in their definition of UTI (27).…”
Section: Urinary Tract Infection In Long-term Care Homesmentioning
confidence: 99%